Pós-tratamento de efluente saneante domissanitário por ozonização convencional e catalítica - Pinheiro, Aline Martins (2014)
The household cleaning effluent from a manufacturing company of cleaners located in Uberlândia/MG was treated with oxidative processes O3/pH7, O3/pH3, O3/pH10, O3/pH3/Fe2+, O3/pH3/Fe3+, O3/pH3/Mn2+, O3/pH10/Activated Carbon 1 g/L and O3/pH10/ Activated Carbon 2 g/L. Also the study of the stripping of volatile organic compounds in the effluent was evaluated with the use of compressed air and pure oxygen as the carrier gas. Results were evaluated in terms of percentage removal of turbidity, COD and true color parameters, the last two being those of greatest interest. Also evaluated whether variations in the values of alkalinity and pH obtained. The spectrum scanning UV-VIS was used as an auxiliary tool of analysis. The COD removal efficiency was low for all the treatments, achieving maximum removal of 7.5%. The low removal efficiencies of organic matter may be associated with low production capacity of O3 in 1.8 gO3/h and the possibility of generation of byproducts of ozonation, not quantized in this work. The color removal reached higher values, with maximum removal achieved around 60%. The homogeneous catalytic ozonation treatment in O3/pH3/Fe3+ system was more efficient both for the decolorization of the effluent and for the oxidation of organic matter higher, possibly by improved interaction of the catalyst with the chemicals found in the analyzed matrix, since the mechanism of the ozonation process is not established tatalmente but varies considerably with the type of metal species used and their interaction with the compounds of the matrix.